2002
DOI: 10.2320/matertrans.43.3005
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Titanium Utilizing a Repassivation Reaction in Aqueous Solutions

Abstract: The surface modification of titanium utilizing repassivation reaction was attempted. The original surface oxide film on titanium plates were mechanically removed under immersion in water and Hanks' solutions with pH 5.0 and 7.4 followed by repassivation or regeneration of surface oxide film in the same solutions. Then the surface-modified titanium plates were immersed in Hanks' solution (pH 7.4) up to 604.8 ks. Their surface was analyzed with scanning electron microscopy with energy dispesive X-ray spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Therefore, surface treatments that do not cause callus formation are necessary for the safe use of Ti alloy devices. It has been reported that zirconium (Zr) forms zirconium phosphate but not calcium phosphate (Hanawa et al 1992(Hanawa et al , 2002b. The coating of Zr inhibits the formation of calcium phosphate on Ti ).…”
Section: Inhibition Of Assimilationmentioning
confidence: 99%
“…Therefore, surface treatments that do not cause callus formation are necessary for the safe use of Ti alloy devices. It has been reported that zirconium (Zr) forms zirconium phosphate but not calcium phosphate (Hanawa et al 1992(Hanawa et al , 2002b. The coating of Zr inhibits the formation of calcium phosphate on Ti ).…”
Section: Inhibition Of Assimilationmentioning
confidence: 99%